Analisis Kualitatif dan Kuantitatif Merkuri dan Timbal pada Sediaan Krim dan Body Lotion Pemutih dengan Mengunakan Spektrofotometer Serapan Atom (SSA) - Haura, Ibtisamah; Utami, Marsah Rahmawati (Poltekkes Kemenkes Padang, 2025)
The use of cosmetics for skin whitening has been widely used by the public, especially made in the form of creams and lotions. Mercury and Lead are included in hazardous materials that if used in large quantities and for a long time will cause harmful side effects. This study aims to assess the qualitative and quantitative analysis methods of mercury (Hg) content in cosmetics based on the data collected. Methods: This research is based on a literature study with an online search for articles with the time of publication of articles from 2014 to 2024 on the Google Scholar database. The results showed that the method of analyzing mercury (Hg) content in cosmetics can be done qualitatively and quantitatively. Qualitative analysis uses KI, NaOH and HCl reagents while quantitative analysis uses Atomic Absorption Spectrophotometry (SSA)/Atomic Absorption Spectrophotometry (AAS) method. Conclusion: analysis of mercury (Hg) content in cosmetics, especially creams and lotions, can be done using qualitative and quantitative analysis using the Atomic Absorption Spectrophotometry (SSA) method because it has good sensitivity to metals. Suggestion: In addition to the use of Atomic Absorption Spectrophotometer (SSA), future studies should consider the use of supporting methods such as Chromatography or UV-Vis Spectrophotometry, ICP and other instruments for comparison, as well as toxicology testing to assess the biological impact of heavy metal content toxicology testing to assess the biological impact of the detected heavy metal content.detected.